EVALUASI PENERAPAN SISTEM PENGENDALIANINTERNAL PERSEDIAAN BARANG DAGANG DENGAN COSO FRAMEWORK PADA PINTU AIR SWALAYAN MAUMERE - Sengari, Maria K. Nini; Dince, Maria Nona; Rangga, Yoseph Darius P. (Jurnal Riset Manajemen dan Akuntansi, 2023)
This study aims to find out whether the implementation of internal control of merchandise inventory at the Self-Service Water Gate (PAS) is in accordance with the COSO Framework (The Committee Of Sponsoring Organization Of Treadway Commission). The type of research used is a type of descriptive research, the type of data used is primary data and secondary data. Data were obtained by observation, interviews and documentation. This research is a research that uses a qualitative descriptive approach. The analysis step is by reducing data, presenting data, and drawing conclusions. The results showed that the application of internal control of merchandise inventory by Maumere Swalayan Water Gate which is in accordance with COSO theory is, control environment, risk assessment, control activities and information and communication. Meanwhile, what is not in accordance with the COSO theory is monitoring.